소비자의 이타주의적 가치관과 자기중심적 가치관이 사회적 책임의식과윤리적 패션제품에 대한 프리미엄 가격 지불의도에 미치는 영향 - 최영현; Yeong-hyeon Choi; 안가영; Ga Young Ahn; 김은혜; Eun-hye Kim; 이규혜; Kyu-hye Lee (한국의류산업학회지, 2020)
The fashion industry is accountable for labor and environment-related issues. With such issues raised, consumers' social responsibility for environmental and labor issues has become an important factor that shapes the perception of companies. This study investigates the relationship between consumer values, concerns regarding social issues, and willingness to pay a premium for ethical fashion products. This study included two exogenous variables of altruistic value and egocentric value. In the conceptual model, consumers’ social responsibility was conceptualized as two constructs of environmental consciousness and labor-issue consciousness. It was then analyzed as mediating variables. Willingness to pay a premium for ethical fashion products was the endogenous variable. Data was collected and analyzed with PLS-SEM from 600 consumers. The assessment of discriminant validity and construct validity using CFA were conducted before analyzing the model. Structural equation modeling results revealed that altruistic value directly influenced environmental consciousness and labor-issue consciousness. However, egocentric value was directly and significantly influenced only by labor-issue consciousness. Both environmental and labor issue consciousness directly influenced customers’ willingness to pay a premium, but did not significantly change their willingness to pay a premium. Two-stage serial mediation analysis results indicated that the constructs did not have a significant mediation effect on the exogenous variables (altruistic value and egocentric value) and the endogenous variable (willingness to pay a premium) for ethical fashion products. This study found the influence of consumer’s personal values on their willingness to pay a higher price for ethical fashion products.